HUBUNGAN ASUPAN MINERAL, INDEKS MASSA TUBUH DAN PERSENTASE LEMAK TUBUH TERHADAP TEKANAN DARAH WANITA USIA SUBUR (Studi di Wilayah Kerja Puskesmas Ngemplak Simongan Semarang) - Fani Rizky Nugraheni; Dina Rahayuning Pangestuti; Sri Achadi Nugraheni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Reproductive age is a period when women are particularly vulnerable to nutritional problems due to various biological conditions such as menstruation, pregnancy, and breastfeeding. High blood pressure in reproductive women is something that has to be aware of due to its relation with the risk of their pregnancy. The purpose of this research is to analyze the relationship between mineral adequacy level, Body Mass Index (BMI), and body fat percentage towards blood pressure in reproductive women in working area of Ngemplak Simongan Community Health Center, Semarang. The research method used in this research is explanatory research with cross-sectional design. The sample collection was conducted by using purposive sampling technique with 77 reproductive women as the samples. Data were analysed using Pearson Product Moment test for normal distributed data and Rank Spearmen test for abnormally distributed data. The results showed that most of the respondents were aged 30-49 years (37.7%), recent education was high school (39.0%), 48.1% of respondents were students, sodium intake (80.5%) and magnesium (77.9%) in moderate category, calcium intake (83.1%) and potassium (87.0%) in the less category, Body Mass Index (36.4%) and body fat percentage (33.8%) mostly in the normal category. The results of bivariate analysis showed that there was a relationship between sodium adequacy level (p = 0,001), magnesium adequacy level (p = 0,001), Body Mass Index (p = 0,001) and diastolic blood pressure, and there is no relationship between calcium adequacy level (p = 0,165), potassium adequacy level (p = 0,415), body fat percentage (p = 0,219) and diastolic blood pressure. Based on the results of this study suggested reproductive women to increase consumption of sources of calcium and potassium and reduce the consumption of foods containing high sodium.